An Empirical Research on Perception of Corporate Executives on Career Development - ROBERT. P, WILLIAM; N. P, DHARSHANA. (The journal of contemporary issues in business and government, 2020)
The research paper titled A Study on Perception of Corporate Executives on Career Development. This paper studies Executive perception towards Career Development. Descriptive research is applied using a convenience method of sampling with 46 respondents. The tools used of the study are mean analysis, frequency analysis, t-test , ANOVA and Regression analysis.From the study it is found that Career Success is influenced by Career Development.